Influence of different conditions of sowing on the formation of productivity of sunflower crops - Гарбар, Л. А.; Горбатюк, Е. М. (Scientific Progress & Innovations, 2017)
The results of studies aimed at studying the influence of different seeding conditions on the formation of productivity of sunflower hybrids under study are presented. Studies were conducted during 2014–2016 in the conditions of the Steppe of Ukraine on black earth of typical low-humus. As a result of the conducted researches it was established that in the conditions of the Steppe of Ukraine on black earth of typical low-humus formation of high yields of sunflower at a level of 2.7 tons/ha, hybrids PR64F50, PR64A15 are provided with the recommended sowing time (when the soil is heated at a depth of 10 cm to 10–12 °C ) and the row spacing is 35 cm.